2011
DOI: 10.1007/s11069-011-9956-8
|View full text |Cite
|
Sign up to set email alerts
|

The post-depositional changes of the onshore 2004 tsunami deposits on the Andaman Sea coast of Thailand

Abstract: The Indian Ocean tsunami flooded the coastal zone of the Andaman Sea and left tsunami deposits with a thickness of a few millimetres to tens of centimetres over a roughly one-kilometre-wide tsunami inundation zone. The preservation potential and the post-depositional changes of the onshore tsunami deposits in the coastal plain setting, under conditions of a tropical climate with high seasonal rainfall, were assessed by reinvestigating trenches located along 13 shore-perpendicular transects; the trenches were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
1
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 158 publications
(94 citation statements)
references
References 66 publications
2
86
1
5
Order By: Relevance
“…Before considering the approximate age intervals of tsunami events, we need to discuss the preservation potential of tsunami deposits at this site. Szczucinski (2012) and Spiske et al (2013) mentioned the preservation potential of tsunami deposits in tropical and temperate climate regions, respectively, and showed that the characteristics of tsunami deposits (thickness and sedimentary structure) degrade over time. Spiske et al (2013) emphasized the significance of the preservation potential in assessing the intervals and frequencies of tsunamis, because tsunami deposits are not necessarily preserved in whole inundated areas.…”
Section: Tsunami Ages and Their Intervalsmentioning
confidence: 99%
“…Before considering the approximate age intervals of tsunami events, we need to discuss the preservation potential of tsunami deposits at this site. Szczucinski (2012) and Spiske et al (2013) mentioned the preservation potential of tsunami deposits in tropical and temperate climate regions, respectively, and showed that the characteristics of tsunami deposits (thickness and sedimentary structure) degrade over time. Spiske et al (2013) emphasized the significance of the preservation potential in assessing the intervals and frequencies of tsunamis, because tsunami deposits are not necessarily preserved in whole inundated areas.…”
Section: Tsunami Ages and Their Intervalsmentioning
confidence: 99%
“…Several studies were also conducted one or more years after a tsunami. However, they are not discussed here because they have not assessed the post-depositional changes that were found to be important in the case of the onshore tsunami deposits in Thailand (Szczuciński et al, , 2007Goto et al, 2008Goto et al, , 2012Jankaew et al, 2008;Szczuciński, 2012), as well as in other parts of the Indian Ocean basin (Nichol and Kench, 2008). This paper has four objectives: -to provide a new documentation of the recent (i.e., not altered by post-depositional processes) onshore tsunami deposits (spatial extent, thickness, sediment structure and texture) from areas flooded by the 2004 IOT that experienced various runup heights, -to interpret the possible tsunami-related sedimentation processes, -to examine if variations in the tsunami runup heights are reflected in the tsunami deposit properties -and to compare the new data with the existing common set of diagnostic features for tsunami deposits.…”
Section: Introductionmentioning
confidence: 99%
“…The uppermost sand sheet (S1) was formed by the IOT in December 2004. All older layers (S2-5) revealed similar sedimentary characteristics as the IOT deposit; differences in geochemistry (zero instead of 8-15 % CaCO 3 ), fossil content (no fossils in the older layers) and geometry (discontinuous extent) can be addressed to post-depositional changes (Szczuciński, 2012). Since the prehistoric sand sheets are interpreted to have the same origin as those described by Jankaew et al (2008) and Fujino et al (2009), they are referred to as tsunamites of unknown age (see Sect.…”
Section: General Stratigraphy and Depositional Environmentsmentioning
confidence: 90%